Endothelial cells activate the cancer stem cell‐associated NANOGP8 pathway in colorectal cancer cells in a paracrine fashion. Issue 8 (6th June 2017) - Wang, Rui; Bhattacharya, Rajat; Ye, Xiangcang; Fan, Fan; Boulbes, Delphine R.; Xia, Ling; Ellis, Lee M.
Abstract : In colorectal cancer (CRC), cancer stem cells (CSCs) have been hypothesized to mediate cell survival and chemoresistance. Previous studies from our laboratory described a role for liver parenchymal endothelial cells (LPECs) in mediating the CSC phenotype in CRC cells in a paracrine/angiocrine fashion. The objectives of this study were to determine whether endothelial cells (ECs) from different organs can induce the CSC phenotype in CRC cells and to elucidate the signaling pathways involved. We treated a newly developed CRC cell line (HCP‐1) and established CRC cell lines (HT29 and SW480) with conditioned medium (CM) from primary ECs isolated from nonmalignant liver, lung, colon mucosa, and kidney. Our results showed that CM from ECs from all organs increased the number of CSCs, as determined by sphere formation, and protein levels of NANOG and OCT4 in CRC cells. With the focus of further elucidating the role of the liver vascular network in mediating the CSC phenotype, we demonstrated that CM from LPECs increased resistance to 5‐fluorouracil in CRC cells. Moreover, we showed that LPEC CM specifically induced NANOGP8 expression in CRC cells by specific enzyme digestion and a luciferase reporter assay using a vector containing the NANOGP8 promoter. Lastly, we found that LPEC CM‐induced NANOGP8 expression and sphere formation were mediated by AKT activation. Our studies demonstrated a paracrine role for ECs in regulating the CSC phenotype and chemoresistance in CRC cells by AKT‐mediated induction of NANOGP8 . These studies suggest a more specific approach to target CSCs by blocking the expression of NANOGP8 in cancer cells. Abstract : Conditioned medium (CM) from endothelial cells (ECs) from nonmalignant liver, lung, colon mucosa, and kidney promoted the cancer stem cell (CSC) phenotype in colorectal cancer (CRC) cells. CM from ECs increased the protein levels of CSC‐associated NANOG and OCT4 in CRC cells. Focusing on CM from liver ECs, we found an increase in CRC cells resistant to 5‐fluorouracil and that AKT activation specifically induced the transcription of NANOGP8.